Konsep Nafkah Menurut Faqihudin Abdul kodir Perspektif Teori Keadilan John Rowls - Nabilah Fikriyah; Zakiyatul Ulya (Institut Agama Islam Negeri Ponorogo, 2025)
The concept of nafkah (financial support) in marriage remains a debated issue, particularly in relation to gender equality and the role of women in the modern era. Law No. 1 of 1974 on Marriage stipulates that the husband is obliged to meet household needs according to his ability. However, some feminists propose a mubadalah (reciprocal) approach to nafkah, emphasizing cooperation between husband and wife. This study aims to explore the concept of nafkah in the mubadalah theory introduced by Faqihuddin Abdul Kodir and its relevance to John Rawls' theory of justice. The article is the result of library research employing a qualitative approach. Collected data was analyzed descriptively using deductive reasoning. The findings indicate that the nafkah concept proposed by Faqihuddin Abdul Kodir offers a more just and proportional approach to sharing family responsibilities, grounded in the principle of reciprocity. It highlights the importance of providing space for women to contribute to family income, ensuring that financial responsibilities are not solely borne by the husband but involve harmonious mutual contributions. Consequently, the role of women, through freedom and opportunity, complements family dynamics, fostering balanced, supportive relationships and strengthening family cohesion. This allows both husband and wife equal opportunities for personal growth while maintaining their essential responsibilities within the family.